Manajemen Event New Year Run 2022 Semarang Runners - Fathoni, Muhammad Ihsan; Qoriah, Anirotul (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to understand the management of the 2022 Semarang Runners new year run event from planning, organizing, monitoring and evaluation. This type of research is descriptive qualitative research. The instruments used are observation, interviews, and documentation. The data sources in this study were the committee and participants who were taken by researchers according to their needs so that it was called purposive sampling research. Data analysis techniques in this study used data reduction, data display and data conclusion drawing/verification. The results showed that: 1) Work program planning was appropriate, target participants were achieved, existing obstacles were handled properly, problem solving went well. 2) Organizing went well from the organizational structure of the committee, tasks in the committee, socialization of activities went well. 3) Supervision has been running both in terms of the monitoring process and the monitoring system. 4) The evaluation is quite good with an evaluation after the activity and notes for improvement in the implementation of the upcoming New Year Run Event. The conclusion of this research is that event management for the new year run 2022 Semarang Runners has been going well. Planning, organizing, monitoring and evaluation are carried out well